Corruption as a collective action problem: Towards a more adjusted approach to thinking about institutional reform in Latin America - Philipps Zeballos, Andy (2018)
I understand, as Kafka does, that the situation of the bureaucracy of the early twentieth century in Europe in 'The trial’, that corruption has as one of its roots the lack of a sense of community. In this article I propose to overcome the rational choice approach. That way I can combine it with one (that) can understand corruption as collective action. That is why I reflect on the next four key questions to understand this approach: A) what is a collective action problem? this detaches that high levels of trust are significantly related with lower levels of corruption. B) When can we talk about societies where corruption is more the norm than an exception? this deduces that confidence is at stake, specially, in institutions. And c) in which degree the environment determines human behavior in relation with social psychology? Thus, this new paradigm addresses institutions of public administration in the middle of anti-corruption policies and provides us of clues about what characteristics are the ones that matter enough to get more confidence, more cooperation and, finally, less corruption in a state.